2008
DOI: 10.2116/analsci.24.871
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Injection Spectrophotometric Determination of Azithromycin in Pharmaceutical Formulations Using p-Chloranil in the Presence of Hydrogen Peroxide

Abstract: A flow-injection (FI) spectrophotometric procedure exploiting merging zones is proposed for the determination of azithromycin in pharmaceutical formulations. The method is based on the reaction of azithromycin with tetrachloro-pbenzoquinone (p-chloranil) accelerated by hydrogen peroxide and conducted in a methanol medium, producing a purplered color compound (lmax = 540 nm). The FI system and the experimental conditions were optimized using a multivariate method. Beer's law is obeyed in a concentration range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Azithromycin has been also studied in 3 studies (7%). HPLC method were useful for 2 of them whereas 1 used UV spectrophotometry which were based on the reaction of azithromycin with p-chloranil in order to obtain a compound colored in red and measurable at the spectrophotometer at 540 nm [27]. [28].…”
Section: Characteristics Of Methods and Active Ingredientsmentioning
confidence: 99%
“…Azithromycin has been also studied in 3 studies (7%). HPLC method were useful for 2 of them whereas 1 used UV spectrophotometry which were based on the reaction of azithromycin with p-chloranil in order to obtain a compound colored in red and measurable at the spectrophotometer at 540 nm [27]. [28].…”
Section: Characteristics Of Methods and Active Ingredientsmentioning
confidence: 99%
“…Este gráfico mostra que o sinal positivo indica que o melhor sinal analítico é obtido quando há um aumento do valor da respectiva variável, enquanto o sinal negativo indica que o melhor sinal é favorecido quando há diminuição desta variável, na faixa pré-estabelecida. 30 Neste sentido, a concentração de HCl e alça de amostragem foram as variáveis que menos influenciaram na reação entre p-DAC e glifosato, por apresentarem efeitos menores que 5%. Desta forma, as mesmas foram fixadas nos níveis mais baixos (-1).…”
Section: Otimização Das Variáveisunclassified
“…[26][27][28] Essa aceitação foi devida à possibilidade deste procedimento propiciar o desenvolvimento de métodos analíticos de melhor precisão empregando equipamentos de baixo custo, bem como a possibilidade do pesquisador desenvolver seu próprio módulo de análise. [29][30][31] Outras vantagens na aplicação dos sistemas em fluxo em relação aos procedimentos existentes na literatura são o pouco uso de vidrarias, a utilização de um sistema fechado, o que minimiza os riscos de contaminação, e o baixo consumo de reagentes, o que o torna um procedimento mais limpo. 32,33 Considerando que o glifosato vem sendo utilizado no Brasil desde 1978, em numerosas condições de agricultura, áreas urbanas, manutenção de estradas e ferrovias, envolvendo inúmeras formulações comerciais, produzidas por empresas com diferentes níveis tecnológicos, o desenvolvimento de métodos rápidos e ambientalmente mais benignos para o controle de qualidade das formulações comerciais deste herbicida é de suma importância para o setor industrial, bem como para o controle de adulterações e/ou falsificações desses produtos.…”
Section: Introductionunclassified
“…This indicated that the variables with no significant effects were the reactor length, pulse interval for the reagent and sample solutions, number pulse of the carrier stream and HCl concentrations, because their influences on the analytical signal magnitudes were smaller than 5%. 38 Therefore, the combination of 80 pulses of the carrier stream, 2 s for the pulse interval of the reagent and the sample solutions, 190 cm of the reactor length, 0.001 mol L -1 of HCl concentration in the reagent solution (solvent) and in the carrier stream were used.…”
Section: -37mentioning
confidence: 99%